Knowledge Of HIV/AIDS Among Patients Attending General Out Patient Department of a Tertiary Care Hospital of Kolkata - Basu, Mausumi; Chatterjee, Sita; Sinha, Debasish; Pal, Bobby; Dutta, Sinjita; Das, Palash (National Journal of Community Medicine, 2014)
Introduction: The total number of people living with HIV/AIDS in India is estimated at 21 lakh in 2011. Now India is on track to achieve the global targets of ‘Zero New Infections, Zero AIDS-related deaths& Zero discrimination.’ The modes of transmission HIV is known and is largely preventable, but due to lack of knowledge about HIV/AIDS in general population makes it’s rapid spread in India. So understanding about the knowledge about HIV/AIDS in general populations will help in formulating strategy for prevention and treatment. Objective: to assess the knowledge about HIV/AIDS among the people attending general OPD in a Tertiary Care Hospital of Kolkata. Methods: An Institution based cross sectional study was conducted among 576 patients attending the General OPDin a tertiary care hospital of Kolkata from February 2013- April 2013 using a predesigned pretested schedule. Results: 100 percent of the study population had heard about HIV/AIDS; more than 90 percent reported that unsafe sex, infected needle sharing, and contaminated blood transfusion were possible ways of transmission. Misconceptions regarding the transmission of were found among more than 25 percent the respondents. More than 70 percent of the participants were aware of various possible correct preventive measures. Electronic media was the main source of information. More than 40 percent respondents knew the major high risk groups. Conclusion: These study results can be useful in directing future efforts at creating awareness about HIV/AIDS.